Characteristics of Instagram Advertising and Intensity of Followers Viewing Advertising Content or Instagram Posts on Purchase Intentions - Indarwati, Tias; Paksi, Yudhistira Rangga; Muhajir, Mohc Velian; Avega, Agatha Christy (CV ODIS, 2021)
The purpose of this study is to determine the chracacteristics of instagram between advertising and intensity of followers viewing advertising content or instagram posts on buying intentions of Kaos polos Surabaya. This study used a sample of 85 respondents. Multiple linear regression in SPSS software was used to analyze the collected data. The results of the study are to show there is a positive and significant chracacteristics of instagram between advertising and intensity of followers viewing advertising content or instagram posts on purcahse intentions of Kaos polos Surabaya..